Evaluation of the Silent Center System Using Cobit 2019 at Disnakertrans Sukabumi Regency With the DSS03 Domain - Raudya Kamila Bilqis; Habi Baturohmah; Hendri Ekasatria (Teknika)
In the digital era, Information Technology (IT) plays a crucial role in improving the efficiency of public services, including at the Dinas Ketenagakerjaan dan Transmigrasi of Sukabumi Regency. One of the service innovations developed is the Silent Center website, which functions as an integrated system for issuing Job Seeker Cards (AK-1). However, this system faces various challenges, such as suboptimal performance, dependence on the main domain, and limitations in IT problem management. This study aims to evaluate the Silent Center system using the COBIT 2019 framework, focusing on the DSS03 – Managed Problems domain. The capability level analysis results indicate that the system's capability level is at Level 3 with a maturity level score of 61.30%, signifying that the system has achieved its purpose in a much more organized manner using organizational assets, with processes typically well-defined. The main issues identified include a lack of IT problem documentation, limited expert personnel, and reliance on vendors. Based on the evaluation results, this study provides improvement recommendations to enhance the efficiency and effectiveness of Silent Center system management, making it more reliable in supporting job seeker services.